The First Wave. Some Aspects of “Disneyfication” in the 1930s - Sitkiewicz, Paweł (Zagadnienia Rodzajów Literackich, 2025)
Although the terms Disneyization or Disneyification in the modern sense were not yet used in the 1930s, when Walt Disney was still a young and independent filmmaker, the beginnings of the Disneyfication of mass culture and animated films could already be observed. However, this phenomenon was perceived differently than in the 1950s or 1990s, when critics and academics focused mainly on the negative or disturbing aspects of this process. The article reconstructs some aspects of the so-called “first wave” of Disneyfication, when Disney films were a positive and shockingly new example of animated cinema as a medium and as a new model of mass culture product. Since the article touches on very broad issues, it is an introduction to the subject. It focuses mainly on those aspects of Disney’s activities that after WWII would become a reason for criticism of the “Disney Magic Kingdom.” These are in particular: the industrialization of film production and the perception of animated films as a new artistic discipline.